Focal points for digital technology integration in early childhood education: implications from practitioners' perspectives - Celik, Osman T.; Candemir, Burcu; Saglam, Mehmet; Tunc, Yunus; Acar, Davut; Kahraman, Umit (Routledge Journals, Taylor & Francis Ltd, 2023)
This study explored the integration of digital technology in early childhood education from the perspectives of 11 preschool teachers using qualitative methods. Through content analysis, four key themes were identified: objectives, multidimensional effects in education, obstacles, and needs/expectations. Teachers employ digital tools to adapt to changes and enhance learning, despite concerns about potential harm. Barriers include administrative support, teacher beliefs, and competencies, as well as educational policies and parent-teacher cooperation. The study recommends the need for in-service and pre-service training for teachers and comprehensive policy development for effective technology integration.
Keywords: Early childhood education; digital technology; integration of technology; teacher's perspective